#TITLE_ALTERNATIVE# - MAULITA BUDIAWATI (NIM 15107030); Pembimbing: Dr. Ir. Dina Anggreni, M.T dan Dr. Irwan Meilano, OSSY
West Java region is one of the areas that is vulnerable to earthquakes because of itÃ‚Â’s position in the subduction area between the Eurasian plate and the Indo Australian plate. West Java region also has some faults which is one of the earthquakes trigger. The understanding of deformation in this region is important because of this potential danger. Observation of deformation in this region of West Java has been done in several observation points. The result from the observation is a velocity vector of displacement data at every point of observation. For a better understanding we need a model that can describe the displacement of a whole land in West Java not just in some observation points. Interpolation process was carried out by the method of moving averages that make up a certain grid in the region of West Java to provide a kontinyu shift data to answering this need. Moving Average interpolation results are obtained and then used as a model for strain analysis using the triangular segments method. Based on the results obtained, the best model of interpolation Moving Average which can provide kontinyu data was performed with a window size of 0.940. The results of strain analysis showed that the deformation in this region is influenced by the postseismic process because of Pangandaran earthquake and tsunami in 2006, the phenomenon of inter-plate subduction, and also by fault activity.